ANALISIS PENGUKURAN DAN STANDAR WAKTU KERJA PADA PELAYANAN PEMBUATAN SURAT DI KANTOR CAMAT KECAMATAN MAKARTI JAYA (STUDI KASUS KABUPATEN BANYUASIN) - Eni Cahyani; Wulan Indriani (JURNAL KOMPETITIF, 2022)
This study aims to determine the standard time for making letters and to analyze the procedures for measuring the standard time of making letters at the Makati Jaya Subdistrict Head Office so as to build the effectiveness of the work of employees in the office in the end to improve services, especially in administrative activities. The implementation of the research uses liberary research and field research methods, the data used are primary and secondary data with data analysis techniques using standard time measurements. The results obtained The normal time per work element for planning the concept of outgoing letters is 0.567 minutes and the next standard time is 0.646 minutes. The normal time for letter approval is 0.561 minutes and the standard time is 0.631 minutes. The normal time of letter numbering takes 0.638 minutes and produces a standard time of 0.717 minutes. The normal time for typing letter drafts is 0.541 minutes and the standard time is 0.617 minutes. Normal time Signing a letter takes 0.597 minutes and creates a standard time of 0.671 minutes. Normal time Stamping takes 0.595 minutes and produces a standard time of 0.678 minutes. Normal time Scheduled a letter for 0.541 minutes and resulted in a standard time of 0.617 minutes. From the results of observations and various data that have been obtained, the process of making outgoing letters obtains a standard time of 4,577 minutes.Keywords: Normal Time; Standard Time; Measurement